Pediatric asthma hospitalization: individual and environmental characteristics of high utilizers in South Texas. (2nd January 2022) - Baek, Juha; Kash, Bita A.; Xu, Xiaohui; Benden, Mark; Roberts, Jon; Carrillo, Genny
Abstract: Objective : Few studies have examined factors affecting the high frequency of hospitalization for pediatric asthma. This study identifies individual and environmental characteristics of children with asthma from a low-income community with a high number of hospitalizations. Methods : The study population included 902 children admitted at least once to a children's hospital in South Texas because of asthma from 2010 to 2016. The population was divided into three groups by utilization frequency (high: ≥4 times, medium: 2–3 times, or low: 1 time). Individual-level factors at index admission and environmental factors were included for the analysis. Unadjusted and adjusted multivariate ordered logistic regression models were applied to identify significant characteristics of high hospital utilizers. Results : The high utilization group comprised 2.4% of total patients and accounted for substantial hospital resource utilization: 10.8% of all admissions and 13.5% of days stayed in the hospital. Patients in the high utilization group showed longer length of stay (LOS) and shorter time between admissions on average than the other two groups. The multivariate ordered logistic regression models revealed that age of 5–11 years (OR = 0.57, 95%CI = 0.35–0.93), longer LOS (2 days: OR = 1.80, 95%CI = 1.15–2.84; ≥3 days: OR = 3.38, 95%CI = 2.10–5.46), warm season at index admission (OR = 1.49, 95%CI = 1.01–2.20), and higher average ozone level in children's residential neighborhoods (OR = 1.78, 95%CI = 1.01–3.14) were significantly associated with a higher number of asthma hospitalizations. Conclusions : The findings suggest the importance of monitoring high hospital utilizers and establishing strategies for such patients based on their characteristics to reduce repeated hospitalizations and to increase optimal use of hospital resources.